Alternative and Online Assessment in the Context of Outcome Based Education: A Practical Guide - Rohana, Sapawi; Azzahrah, Anuar; Rafeah, Wahi; Nur Tahirah, Razali; Mohd Hafizan, Hashim (Science Research Society, 2021)
Alternative assessment measures the learner’s ability and proficiency in performing complex tasks that are related to the intended learning outcomes and relies on direct measures of target skills in a specific knowledge or skill-domain. Meanwhile, online assessment is an assessment conducted in an online environment on a fully automated platform. Both types of assessments are getting a substantial attention worldwide due to their many advantages. However, several factors must be taken into consideration in implementing the alternative and online assessment in an outcome-based education (OBE) system. Thus, this paper provides a practical guide to alternative and online assessment in the context of OBE -including the constructive alignment, student learning time and development ofassessment rubrics. Other considerations are also discussed, namely the validity and reliability of the alternative and online assessment, and deterring plagiarism and cheating.